'Tell me about your pain': abdominal pain and a history of bullying. (24th March 2011) - Rosati, Paola; Jenkner, Alessandro; De Vito, Rita; Boldrini, Renata; Chiodi, Patrizia; Celesti, Lucia; Giampaolo, Rosaria
Abstract : A 7-year-old girl was brought to our outpatient clinic to investigate recurrent abdominal pain. She was unwilling to attend the school. Her mother reported bullying at school and nosebleeds. The girl rated her pain 9 on a visual analogue score card ranging from 1 to 10. Physical examination disclosed painful bruising and haematomas. Emergency laboratory blood tests indicated by the history, physical examination and the pain intensity showed reduced numbers of white blood cells and platelets. A bone marrow smear on admission disclosed 100% blasts and suggested an initial diagnosis of leukaemia but also disclosed the pseudo-rosettes typically seen in neuro-ectodermic tumours. The diagnosis of stage IV primary neuroblastoma was confirmed by trephine biopsies and high urinary catecholamines. The girl died 10 months later. This unusual case underlines the need for outpatient paediatricians to involve children in their initial diagnostic work-up by asking them about their pain thus expediting the diagnosis.